Context-dependent trade-offs in body size among Olympic sports - Kipp, Shalaya; Husen, Martin; Wiggins, Chad C.; Gorman, Ellen K.; Clayburn, Andrew J.; Joyner, Michael J.; Senefeld, Jonathon W. (Applied physiology, nutrition, and metabolism, 2025)
There is a context-dependent trade-off in body size of elite runners, such that smaller body sizes are observed among longer distance runners. However, it is unclear whether this trade-off in body size is observed in other Olympic sports, such as cycling and swimming. To understand the association between body size and athletic competition, we examined metrics of body size from male and female Olympic athletes competing in swimming, running, and cycling. We collected standard anthropometrics (height, mass, body mass index (BMI), and body surface area) of elite male and female athletes competing in the London 2012 Summer Olympics from a public repository. Anthropometric data were compared between sexes (male and female); between sports (swimming, running, and cycling); and between distances within sports (shorter and longer distance). Males were taller (P < 0.001), heavier (P < 0.001), and had a larger BMI (P < 0.001) compared to females. Relative to athletes competing in longer distance events, athletes competing in shorter distance were generally taller (running: P < 0.001, swimming: P ≤ 0.014) and heavier (running: P < 0.001, swimming: P = 0.002 (males) and P = 0.148 (females), cycling: P < 0.001) for both males and females. Height was not different between shorter and longer distance cyclists. There was a trade-off between body size and distance for each of the three Olympics sports, such that smaller athletes were observed in longer distance events. Although there were large sex-based differences in body size, similar trade-offs in size and event were observed for both males and females. These data suggest that there is an optimal combination of skeletal muscle mass and body size to optimize movement economy that is generally preserved across different modes of human locomotion.
Veröffentlicht: 23. Juli 2025
Gesehen am 19.11.2025